Runge-Kutta method for higher-order differential equations
up vote
1
down vote
favorite
I am studying Numerical Analysis with the book of Richard L.Burden.
A question which I'm struggling with right now is following.
Transform the second-order initial-value problem
$y'' - 2y' + 2y = e^{2t}sin t$ for $0 leq t leq 1, $ with $y(0) = -0.4, y'(0) = -0.6, h=0.1$
into a system of first order initial-value problems, and use the Runge-Kutta method ith h=0.1 to approximate the solution.
Then,
$$u_1(t) = y(t), u_2(t) = y'(t)$$
$$u_1'(t) = u_2(t)$$
$$u_2'(t) = e^{2t}sin t - 2u_1(t) + u_2(t)$$
$$u_1(0) = -0.4, u_2(0) = -0.6$$
This initial conditions give $w_{1,0} = -0.4, w_{2,0}=-0.6$
I can understand that $k_{1,1} = hf_1(t_0, w_{1,0}, w_{2,0}) = hw_{2,0}$
$f_1 = u_1'= u_2(t)$,
So $f_1(t_0, w_{1,0}, w_{2,0}) = u_2(t_0, w_{1,0}, w_{2,0}) = w_{2,0}$ (By definition of $w_{i,j}$)
However, I can't understand the following.
$$k_{2,1} = hf_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}) = hleft[w_{2,0} + frac{1}{2}k_{1,2}right]$$
Why does $f_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2})$ equal to $w_{2,0} + frac{1}{2}k_{1,2}$? It seems that third argument in the function comes out, but there is no detailed explanation in this book.
runge-kutta-methods
add a comment |
up vote
1
down vote
favorite
I am studying Numerical Analysis with the book of Richard L.Burden.
A question which I'm struggling with right now is following.
Transform the second-order initial-value problem
$y'' - 2y' + 2y = e^{2t}sin t$ for $0 leq t leq 1, $ with $y(0) = -0.4, y'(0) = -0.6, h=0.1$
into a system of first order initial-value problems, and use the Runge-Kutta method ith h=0.1 to approximate the solution.
Then,
$$u_1(t) = y(t), u_2(t) = y'(t)$$
$$u_1'(t) = u_2(t)$$
$$u_2'(t) = e^{2t}sin t - 2u_1(t) + u_2(t)$$
$$u_1(0) = -0.4, u_2(0) = -0.6$$
This initial conditions give $w_{1,0} = -0.4, w_{2,0}=-0.6$
I can understand that $k_{1,1} = hf_1(t_0, w_{1,0}, w_{2,0}) = hw_{2,0}$
$f_1 = u_1'= u_2(t)$,
So $f_1(t_0, w_{1,0}, w_{2,0}) = u_2(t_0, w_{1,0}, w_{2,0}) = w_{2,0}$ (By definition of $w_{i,j}$)
However, I can't understand the following.
$$k_{2,1} = hf_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}) = hleft[w_{2,0} + frac{1}{2}k_{1,2}right]$$
Why does $f_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2})$ equal to $w_{2,0} + frac{1}{2}k_{1,2}$? It seems that third argument in the function comes out, but there is no detailed explanation in this book.
runge-kutta-methods
add a comment |
up vote
1
down vote
favorite
up vote
1
down vote
favorite
I am studying Numerical Analysis with the book of Richard L.Burden.
A question which I'm struggling with right now is following.
Transform the second-order initial-value problem
$y'' - 2y' + 2y = e^{2t}sin t$ for $0 leq t leq 1, $ with $y(0) = -0.4, y'(0) = -0.6, h=0.1$
into a system of first order initial-value problems, and use the Runge-Kutta method ith h=0.1 to approximate the solution.
Then,
$$u_1(t) = y(t), u_2(t) = y'(t)$$
$$u_1'(t) = u_2(t)$$
$$u_2'(t) = e^{2t}sin t - 2u_1(t) + u_2(t)$$
$$u_1(0) = -0.4, u_2(0) = -0.6$$
This initial conditions give $w_{1,0} = -0.4, w_{2,0}=-0.6$
I can understand that $k_{1,1} = hf_1(t_0, w_{1,0}, w_{2,0}) = hw_{2,0}$
$f_1 = u_1'= u_2(t)$,
So $f_1(t_0, w_{1,0}, w_{2,0}) = u_2(t_0, w_{1,0}, w_{2,0}) = w_{2,0}$ (By definition of $w_{i,j}$)
However, I can't understand the following.
$$k_{2,1} = hf_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}) = hleft[w_{2,0} + frac{1}{2}k_{1,2}right]$$
Why does $f_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2})$ equal to $w_{2,0} + frac{1}{2}k_{1,2}$? It seems that third argument in the function comes out, but there is no detailed explanation in this book.
runge-kutta-methods
I am studying Numerical Analysis with the book of Richard L.Burden.
A question which I'm struggling with right now is following.
Transform the second-order initial-value problem
$y'' - 2y' + 2y = e^{2t}sin t$ for $0 leq t leq 1, $ with $y(0) = -0.4, y'(0) = -0.6, h=0.1$
into a system of first order initial-value problems, and use the Runge-Kutta method ith h=0.1 to approximate the solution.
Then,
$$u_1(t) = y(t), u_2(t) = y'(t)$$
$$u_1'(t) = u_2(t)$$
$$u_2'(t) = e^{2t}sin t - 2u_1(t) + u_2(t)$$
$$u_1(0) = -0.4, u_2(0) = -0.6$$
This initial conditions give $w_{1,0} = -0.4, w_{2,0}=-0.6$
I can understand that $k_{1,1} = hf_1(t_0, w_{1,0}, w_{2,0}) = hw_{2,0}$
$f_1 = u_1'= u_2(t)$,
So $f_1(t_0, w_{1,0}, w_{2,0}) = u_2(t_0, w_{1,0}, w_{2,0}) = w_{2,0}$ (By definition of $w_{i,j}$)
However, I can't understand the following.
$$k_{2,1} = hf_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}) = hleft[w_{2,0} + frac{1}{2}k_{1,2}right]$$
Why does $f_1(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2})$ equal to $w_{2,0} + frac{1}{2}k_{1,2}$? It seems that third argument in the function comes out, but there is no detailed explanation in this book.
runge-kutta-methods
runge-kutta-methods
edited Nov 19 at 18:18
LutzL
54.7k42053
54.7k42053
asked Nov 19 at 7:34
James
82
82
add a comment |
add a comment |
1 Answer
1
active
oldest
votes
up vote
0
down vote
accepted
In this problem, I think what you might be confusing is that we have
$$begin{align} u_1'(t) &= u_2(t) = f_1(t, u_1, u_2) \ u_2'(t) &= e^{2t} sin t - 2 u_1(t) + 2 u_2(t) = f_2(t, u_1, u_2) end{align}$$
From this, we can see that for all the iterations of $j$ on $f_1$, we have
$$f_1(t, u_1, u_2) = f_1(u_2) = w_{2,j} tag{1}$$
That is, $f_1$ will only ever have $u_2$ terms, which do not depend on $t$ explicitly or $u_1$, thus the iteration formula reduces to
$$k_{2,1} = hf_1left(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}right) = hf_1left(w_{2,0} + frac{1}{2}k_{1,2}right)$$
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
1
I got it. Thanks for answering
– James
Nov 20 at 2:15
add a comment |
1 Answer
1
active
oldest
votes
1 Answer
1
active
oldest
votes
active
oldest
votes
active
oldest
votes
up vote
0
down vote
accepted
In this problem, I think what you might be confusing is that we have
$$begin{align} u_1'(t) &= u_2(t) = f_1(t, u_1, u_2) \ u_2'(t) &= e^{2t} sin t - 2 u_1(t) + 2 u_2(t) = f_2(t, u_1, u_2) end{align}$$
From this, we can see that for all the iterations of $j$ on $f_1$, we have
$$f_1(t, u_1, u_2) = f_1(u_2) = w_{2,j} tag{1}$$
That is, $f_1$ will only ever have $u_2$ terms, which do not depend on $t$ explicitly or $u_1$, thus the iteration formula reduces to
$$k_{2,1} = hf_1left(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}right) = hf_1left(w_{2,0} + frac{1}{2}k_{1,2}right)$$
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
1
I got it. Thanks for answering
– James
Nov 20 at 2:15
add a comment |
up vote
0
down vote
accepted
In this problem, I think what you might be confusing is that we have
$$begin{align} u_1'(t) &= u_2(t) = f_1(t, u_1, u_2) \ u_2'(t) &= e^{2t} sin t - 2 u_1(t) + 2 u_2(t) = f_2(t, u_1, u_2) end{align}$$
From this, we can see that for all the iterations of $j$ on $f_1$, we have
$$f_1(t, u_1, u_2) = f_1(u_2) = w_{2,j} tag{1}$$
That is, $f_1$ will only ever have $u_2$ terms, which do not depend on $t$ explicitly or $u_1$, thus the iteration formula reduces to
$$k_{2,1} = hf_1left(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}right) = hf_1left(w_{2,0} + frac{1}{2}k_{1,2}right)$$
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
1
I got it. Thanks for answering
– James
Nov 20 at 2:15
add a comment |
up vote
0
down vote
accepted
up vote
0
down vote
accepted
In this problem, I think what you might be confusing is that we have
$$begin{align} u_1'(t) &= u_2(t) = f_1(t, u_1, u_2) \ u_2'(t) &= e^{2t} sin t - 2 u_1(t) + 2 u_2(t) = f_2(t, u_1, u_2) end{align}$$
From this, we can see that for all the iterations of $j$ on $f_1$, we have
$$f_1(t, u_1, u_2) = f_1(u_2) = w_{2,j} tag{1}$$
That is, $f_1$ will only ever have $u_2$ terms, which do not depend on $t$ explicitly or $u_1$, thus the iteration formula reduces to
$$k_{2,1} = hf_1left(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}right) = hf_1left(w_{2,0} + frac{1}{2}k_{1,2}right)$$
In this problem, I think what you might be confusing is that we have
$$begin{align} u_1'(t) &= u_2(t) = f_1(t, u_1, u_2) \ u_2'(t) &= e^{2t} sin t - 2 u_1(t) + 2 u_2(t) = f_2(t, u_1, u_2) end{align}$$
From this, we can see that for all the iterations of $j$ on $f_1$, we have
$$f_1(t, u_1, u_2) = f_1(u_2) = w_{2,j} tag{1}$$
That is, $f_1$ will only ever have $u_2$ terms, which do not depend on $t$ explicitly or $u_1$, thus the iteration formula reduces to
$$k_{2,1} = hf_1left(t_0 + frac{h}{2}, w_{1,0} + frac{1}{2}k_{1,1}, w_{2,0} + frac{1}{2}k_{1,2}right) = hf_1left(w_{2,0} + frac{1}{2}k_{1,2}right)$$
edited Nov 19 at 18:16
answered Nov 19 at 16:41
Moo
5,46131020
5,46131020
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
1
I got it. Thanks for answering
– James
Nov 20 at 2:15
add a comment |
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
1
I got it. Thanks for answering
– James
Nov 20 at 2:15
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Why does f_1 depend only on u_2? Does the formula u_2(t) = f_1(t, u_1, u_2) mean that f_1 depends only on u_2?
– James
Nov 20 at 0:48
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
Yes, because $f_1 = u_2$, there is nothing like $f_1 = e^t(u_1 + u_2)$, for example, in which case $f_1$ would depend on all three, namely $t, u_1 ~ text{and}~ u_2$. In this problem, we have $f_1 = u_2$ only - it is how it was setup in the very beginning. Clear?
– Moo
Nov 20 at 1:12
1
1
I got it. Thanks for answering
– James
Nov 20 at 2:15
I got it. Thanks for answering
– James
Nov 20 at 2:15
add a comment |
Thanks for contributing an answer to Mathematics Stack Exchange!
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
Use MathJax to format equations. MathJax reference.
To learn more, see our tips on writing great answers.
Some of your past answers have not been well-received, and you're in danger of being blocked from answering.
Please pay close attention to the following guidance:
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
To learn more, see our tips on writing great answers.
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3004621%2frunge-kutta-method-for-higher-order-differential-equations%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown